Low-temperature VUV photoluminescence and thermoluminescence of UV excited afterglow phosphor Sr3AlxSi1−xO5:Ce3+, Ln3+ (Ln = Er, Nd, Sm, Dy and Tm). Issue 23 (21st June 2015) - Luo, Hongde; Bos, Adrie J. J.; Dobrowolska, Anna; Dorenbos, Pieter
<x xml:space="preserve">Abstract</x> Low-temperature thermoluminescence measurements of Ce doped Sr3SiO5 show that Ce3+ is the recombination centre and Nd, Sm, Dy and Tm work as electron traps with trap depths of 0.95 eV, 1.89 eV, 1.02 eV, and 1.19 eV, respectively.